2006
DOI: 10.2214/ajr.04.1009
|View full text |Cite
|
Sign up to set email alerts
|

Importance of Evaluating All Vascular Phases on Contrast-Enhanced Sonography in the Differentiation of Benign from Malignant Focal Liver Lesions

Abstract: Evaluation of SonoVue enhancement in all three vascular phases is superior to evaluation of SonoVue enhancement in the late phase alone, especially in patients with chronic liver disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
98
1
7

Year Published

2007
2007
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 152 publications
(108 citation statements)
references
References 28 publications
2
98
1
7
Order By: Relevance
“…Hence the portal and late phases may provide more information in the detection of small lesions in cirrhotic liver [24,25] . Evaluation of all three vascular phases has been shown to be superior to the evaluation of enhancement in the late phase alone: the sensitivity increased from 78% to 98%, and the accuracy from 81% to 93% [33] . In a study of 41 cirrhotic patients with small monofocal lesions smaller than 3 cm in diameter using contrast-enhanced Doppler ultrasound, the Table 2 Different phases of liver in contrast-enhanced ultrasound intra-tumoral arterial blood flow was detected in 95% of HCCs, compared with 28% of nonmalignant nodules [34] .…”
Section: Detection Of Malignant Flls In Cirrhotic Liver With Ceusmentioning
confidence: 99%
“…Hence the portal and late phases may provide more information in the detection of small lesions in cirrhotic liver [24,25] . Evaluation of all three vascular phases has been shown to be superior to the evaluation of enhancement in the late phase alone: the sensitivity increased from 78% to 98%, and the accuracy from 81% to 93% [33] . In a study of 41 cirrhotic patients with small monofocal lesions smaller than 3 cm in diameter using contrast-enhanced Doppler ultrasound, the Table 2 Different phases of liver in contrast-enhanced ultrasound intra-tumoral arterial blood flow was detected in 95% of HCCs, compared with 28% of nonmalignant nodules [34] .…”
Section: Detection Of Malignant Flls In Cirrhotic Liver With Ceusmentioning
confidence: 99%
“…Doppler ultrasonography provides information on hepatic and portal vessel patency. Recent studies reported that contrast enhanced ultrasonography provides sensitive and specific criteria for the differentiation between malignant and benign liver lesions [12][13][14][15] . Preliminary data for cholangiocarcinoma suggest a behavior that is not dissimilar to metastatic lesions [14,16] .…”
Section: Ultrasonographymentioning
confidence: 99%
“…When contrast agents are used, the sensitivity and specificity improve significantly and become comparable to those of CT [5]. Assessment of the hepatic vasculature throughout the early and late phases is critical for characterizing these lesions [10].…”
Section: Discussionmentioning
confidence: 99%